Battered women's valuations on health care received - Juana Robledo Martín; Ana Belén Salamanca Castro; Sara Sánchez Castro; Diana de la Fuente Aparicio (Fundación para el Desarrollo de la Enfermería, 2010)
Violence against women in Spain is currently a problem of state public health and of great social concern because of numerous cases of women murdered by their partners or former partners. The objective of this study was to study the perceptions of battered women on health care received.To achieve that aim a qualitative study was developed as the study population were battered women who lived in the Comunidad de Madrid. Data were collected by the performance of focus groups and deep interviews. The women in our study identified health care with assistance provided only in case of physical injuries. Somatizations that abuse occurs were treated by sanitary professionals without addressing the causes that produce them, however, expressed for something more than the professionals who attended, though the women were not able to verbalize to them. The women believed that every healthcare professional has a specific function, therefore, addressed whether mental health professionals without being specialists in this field, was a "matter of luck." It is evident that the actual biopsychosocial concept of health has no draft in the population, or health professionals, making health care was highly valued by them because they solved the specific problems that require assistance.